Research on the Dilemmas and Breakthrough Paths of Two-Way Bridging between Kindergarten and Primary School from the Perspective of Collaborative Education - Hasitana; Li, Yanli (Pacific International Journal, 2025)
The transition from early childhood education to compulsory education is a critical link profoundly impacting children's physical and mental development. The concept of "two-way bridging" aims to break the limitations of the traditional one-sided approach and promote collaborative education between kindergartens and primary schools. From the perspective of synergy theory, and through questionnaires and in-depth interviews, this paper systematically analyzes the main dilemmas faced by the current two-way bridging process across four subsystems: curriculum, teachers, parents, and policy. The study finds that issues such as a disjointed curriculum system, lack of teacher collaboration mechanisms, prominent parental educational anxiety, and weak policy implementation seriously hinder the effective execution of two-way bridging. Based on this, the paper constructs a "four-in-one" collaborative path from the dimensions of curriculum co-development, teacher collaboration, parental guidance, and policy optimization to promote scientific kindergarten-primary school transition and provide theoretical reference and practical guidance for achieving a smooth transition for children.